Technological modernization in irrigated agriculture: factors for sustainability in developing countries - Yap-Salinas, L. Humberto, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
Technology has much to offer to irrigated agriculture in developing countries. Many technological advances have been introduced into practice in these countries. National governments have often played an important role in this process by investing in modern equipment needed by their irrigation districts. Computers, meteorological monitoring stations, and GIS, to mention just a few examples, are used in transferred irrigation districts ranging from large to small, in different climatological and hydrological settings, and by users of varying degrees of education. At first glance, all this would appear to signal success, particularly at the end of a project. In some countries, such as Chile and Mexico, modernization efforts have helped the agricultural sector become more competitive in the global market. However, in other countries, modernization efforts and investments have failed to achieve their goals of improving agricultural production at a competitive level. Thus, there have been considerable successes, but there have also been gaps in this transfer of technology. This paper examines this troubling situation from first-hand experience, and it looks at lessons learned from experience gained in introducing technology along with water users organization in developing countries. Factors that help ensure sustainability of technological modernization in irrigated agriculture in developing countries are discussed, and suggestions are given to make investments in this modernization process more effective in the long term.
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."